Latihan Senam Low-Impact Pada Perempuan Dengan Obesitas - Esri Rusminingsih; Supardi; Marwanti (Universitas Muhammadiyah Klaten, 2023)
Individuals with obesity will experience stress on weight-bearing joints such as the pelvis, knees, and vertebrae which are risk factors for osteoarthritis. Low-impact gymnastics is a type of exercise that is done without causing stress on the joints that support body weight, so it is suitable for individuals with obesity. This community service aims to provide low-impact exercise to members of the Aisiyah branch in Mendak, Delanggu District. Methods: Low-impact exercise was performed on women with BMI > 23 kg/m2. Low-impact aerobic exercise was done in 2 sessions in 1 hour, consisting of 10-15 minutes of warm-up phase, 30-35 minutes of core exercises, and a cooling phase for 10 minutes. At the end of the activity, participants were evaluated for pain response and asked to mention the types of low-impact exercise movements. Results: Low-impact aerobic exercise was attended by 31 participants with an average age of 54.23 ± 8.73 SD and body mass index (BMI) of 24.23 ± 2.12 SD. All participants enthusiastically followed all gymnastic activities until completion. After gymnastics, participants had an average pain level of 0.68 ± 1.107 SD. Participants were able to mention 5 types of low-impact gymnastics movements that were taught.